The universal coding method in the data compression algorithm - Kasumov, N. K. (Automatic control and computer sciences, 2010)
A brand new constructive data compression algorithm is considered. The model’s basic elements are indicated. Data transformation is carried out on the basis of three parameters using binary and decimal numeration systems. Methodical validation of data packing procedures is provided in a generalized form. Step-by-step structural description of the designed model is presented, along with schemes of the logging mechanism and interaction of the algorithm’s main parts. The problem of combining the universalism principle with supercompression of digital information is approached. Moreover, the model operates in modes of both single and multiple application of the same crypto-graphic scenario. A brief analysis of the model under extreme loads with and without considering the decoding log capacities and stabilizing bit array is carried out. The algorithm’s excesses and their effect on data coding and decoding processes efficiencies are discovered. Positive and negative aspects of the introduction of log and stabilizing bits into data compression process are indicated. The concept of information’s critical volume, which specifies the algorithm’s operation in the cryptographic generator mode, is defined.